Developing a Minimum Competency Assessment in Science Literacy: A Rasch-Model Approach on Elements, Compounds, and Mixtures - Rizki Nor Amelia; Nirma Yuliana Saputri (Unnes Science Education Journal, 2026)
This study aims to develop a Minimum Competency Assessment (AKM) instrument for science literacy on the topic of elements, compounds, and mixtures using the Rasch Model. The research followed the 4D development model (Define, Design, Development, and Disseminate). The instrument initially consisted of 25 AKM-format items validated by five junior high school science teachers through expert appraisal using Aiken’s V. The content validity results indicated that 22 items were valid, while three were eliminated for not aligning with the science literacy indicators. Empirical testing was conducted with 175 eighth-grade students from SMP Negeri 1 Juwana. The Rasch analysis showed high reliability (item reliability = .94; model reliability = .95), and all items met the model fit criteria based on the Infit and Outfit MNSQ values. The item difficulty ranged from very easy to very difficult (−1.28 to +1.60 logit), demonstrating a balanced distribution. The developed AKM-based science literacy instrument is valid, reliable, and pedagogically applicable. It can serve as both an evaluation tool and a learning support instrument that fosters critical thinking and scientific reasoning skills, aligning with the AKM and PISA 2025 frameworks.